Oxidative Balance Score and New-Onset Type 2 Diabetes Mellitus in Korean Adults without Non-Alcoholic Fatty Liver Disease: Korean Genome and Epidemiology Study-Health Examinees (KoGES-HEXA) Cohort - Mid-Eum Moon; Dong Hyuk Jung; Seok-Jae Heo; Byoungjin Park; Yong Jae Lee (MDPI AG, 2024)
The oxidative balance score (OBS) is a novel composite of pro- and anti-oxidative markers for assessing the risk of cardiometabolic diseases and non-alcoholic fatty liver disease (NAFLD). However, it has not yet been established whether the OBS is related to type 2 diabetes mellitus (T2DM), especially in a population without NALFD. Therefore, we aimed to investigate the longitudinal effect of the OBS on T2DM in a large cohort of Korean adults without NALFD. Data were assessed from 9798 participants without NALFD from the Korean Genome and Epidemiology Study-Health Examinees (KoGES-HEXA) cohort. The participants were divided into three groups according to OBS tertiles, identified as T1-T3. We prospectively assessed the hazard ratios (HRs) with 95% confidence intervals (CIs) for new-onset T2DM using multivariable Cox proportional hazard regression models over 6 years following the baseline survey. During the mean 3.5 years of follow-up, 145 individuals (1.48%; 56 men and 89 women) developed T2DM. The HRs of T2DM for the OBS tertiles were 0.79 (95% CI, 0.53-1.18) and 0.60 (95% CI, 0.39-0.93) in the T2 and T3 groups after adjusting for metabolic parameters in subjects without NALFD, respectively; however, the T2 group did not show statistical significance toward a decrease in incident T2DM. A low OBS may be a useful predictive marker in new-onset T2DM for middle-aged and older subjects without NALFD. This implies that the OBS could be an additional valuable tool for assessing the incidence of T2DM among individuals without NAFLD.